Explaining Fibrofog: Carbohydrate Cravings Explain More Than Pain and Negative Mood Alone. Issue 1 (3rd April 2015) - Bell, Tyler; Shelley-Tremblay, John; Christensen, Larry
Abstract: Objective : The purpose of the preliminary study was to identify the contributions of various food cravings with the cognitive impairment in fibromyalgia [FMS] known as "Fibrofog". Methods : Forty-seven, non-diabetic female participants aged 19 and older with FMS completed the Mental Clutter Scale, the Food Craving Inventory, the Profile of Mood States and the Fibromyalgia Impact Questionnaire-Revised. Results : Carbohydrate cravings were found to be a unique correlate of Fibrofog compared to other specific cravings. Results from hierarchal models revealed that carbohydrate cravings independently predicted Fibrofog, albeit modestly, over and above the symptoms of physical impact and mood (even after controlling for BMI). Conclusions : Along with the primary roles of FMS symptom clusters, carbohydrate cravings play a unique role in the cognitive impairment.